Functional Effectiveness of Inpatient Rehabilitation After Heart Transplantation. Issue 9 (12th February 2016) - Gupta, Saurabh; Larsen, Elizabeth; Garg, Ankur; John, Florence; Bansal, Mukesh; Eckman, Peter M.; Sembrano, Roderick
Abstract: Background: Heart transplantation (HT) is the treatment of choice for many patients with end‐stage heart failure who remain symptomatic despite optimal medical therapy, but no study has looked directly into functional improvement of HT patients after an inpatient rehabilitation program. Objective: To determine functional improvement in HT patients who completed an inpatient rehabilitation program. Design: Retrospective study. Setting: An inpatient rehabilitation facility (IRF) associated with a tertiary care hospital. Patients: Seventeen patients admitted between March 2011 and September 2014 after HT. Methods: Demographic, clinical, and functional data (admission and discharge Functional Independence Measure [FIM] scores) were recorded. Change in FIM scores and FIM efficiency (change in FIM score/length of stay) were analyzed. FIM outcomes for HT patients were compared with regional and national averages for patients undergoing an inpatient rehabilitation program for cardiac debility. As a secondary outcome, we evaluated whether body mass index of HT patients had an impact on FIM gains in an IRF. Individual FIM items were analyzed for trends. Results are reported as mean ± SD. Results: Twelve male and 5 female patients with mean age of 61.2 ± 4.5 years were identified. Three patients were readmitted to acute hospital because of complications. For those 14 patients who completed the IRF stay, the mean admission and discharge motor FIM were 51.5 (±14.6) and 74.7 (±12.0), respectively. The mean admission and discharge cognition FIM were 30.9 (±3.2) and 32.9 (±1.7), respectively. The mean total FIM gain was 26.9 ± 13.3 ( P < .05). The mean FIM efficiency was 3.2 (±2.0). After admission to an IRF, 82% were discharged home with statistically significant improvement in their functional ability. In addition, all individual FIM items improved from admission to discharge. There was positive relationship between body mass index and FIM gain but this was not statistically significant. Conclusions: An inpatient rehabilitation program appears to positively impact optimal outcomes (functional recovery and discharge to home) for selected patients with HT and is comparable with regional and national FIM gain and efficiency for patients admitted to IRFs with other cardiac conditions.